Do campo à universidade: os critérios de valor musical em Bem Sertanejo - Iara Nayra Couto Sá (2018)
This research has as main objective of understanding how the TV Globo's production, Bem Sertanejo, evidences forms of valuation and social recognition for the sertanejo genre. Based on the concept of musical genre as a cultural category, present in the researches of authors such as Fabbri (2006), Frith (1998) and Janotti Jr. (2003), what is intended is to perceive how the musical community formed around Bem Sertanejo classifies the sertanejo genre and generates clues for its valuation and hierarchy as musical practice. In order to do so, we visit the history of the genre and its relations with Brazilian television and discuss issues related to the valuation and hierarchical practices of cultural products. As an analytical methodology, the Mittell's (2004) proposition was used regarding generic circularity and a corpus composed of several discursive sources that relate to the chosen empirical object.